Distinct Patterns of Picocyanobacterial Communities in Winter and Summer in the Chesapeake Bay - Cai, Haiyuan (American Society for Microbiology (ASM), 2010)
In the Chesapeake Bay, picocyanobacteria were usually 100-fold less abundant in winter than in summer. However, little is known about how picocyanobacterial populations shift between winter and summer in the bay. This is due mainly to undetectable winter picocyanobacterial populations in bacterial 16S rRNA clone libraries. In this study, the winter and summer picocyanobacterial populations in the bay were detected using picocyanobacterium-specific primers and were compared based on the analysis of rRNA internal transcribed spacer sequences. Temperature was found to be the dominant environmental factor controlling picocyanobacterial populations in the Chesapeake Bay. In the summer, marine cluster B Synechococcus dominated the upper bay, while a unique cluster, CB1 (marine cluster A [MC-A] Synechococcus), made up the vast majority in the middle and lower bay. In the winter, the picocyanobacteria shifted to completely different populations. Subclades CB6 and CB7, which belong to MC-A Synechococcus and Cyanobium, respectively, made up the entire winter picocyanobacterial populations in the bay. Interestingly, the winter members in subclade CB6 clustered closely with Synechococcus CC9311, a coastal strain known to have a greater capacity to sense and respond to changing environments than oceanic strains.